Sátira y política en el primer republicanismo: los tres juicios de Juan Martínez Villergas (1840-1854) - Xavier Andreu Miralles (Cuadernos de Ilustración y Romanticismo)
This article analyzes the relevance of satire in the political culture of the first Spanish republicanism through the figure of Juan Martínez Villergas (1817-1894), the best known satirist of mid-nineteenth century Spain. It points out the meaning and usefulness of this literary genre for this political culture. Likewise, it highlights how the confluence between political and literary activities configured a certain model of revolutionary poet and a certain understanding of literature that began to be questioned and cornered in postrevolutionary Spain, under the cultural hegemony of Spanish “respectable” liberalism.